Istiklal Avenue's Intangible Dimensions Related To Cultural Memory - Sav, Sedef; DEMİR, ELİF GELMEZ (My University, 2018)
Urban landscapes include social and cultural practices and values and the intangible dimensions of heritage as related to diversity and identity. According to UNESCO, all these practices, representations, expressions, knowledge, skills as well as the instruments, objects, artefacts and cultural spaces, that communities, groups, and in some cases, individuals recognize as part of their cultural heritage. Through these cultural system elements that base the society's origins, the society links with the past and its previous generations. The intangible heritage, transmitted from generation to generation, is constantly recreated by communities and groups in response to their environment, their interaction with nature and their history, and provides them with a sense of identity and human creativity. istiklal Avenue in other words "Cadde-i Kebir/ Grande Rue de Pera ”, located in the historic Pera region, is among the significant areas with both tangible and intangible features regard to cultural heritage in Istanbul. Beyoğlu has hosted great civilizations throughout the history such as Roman Empire, Ottoman Empire. During the Ottoman Period, because of increase in Istanbul population and embassies were not asked to stay in Bab-ı Ali area most of the embassies resided in Beyoğlu in the 15th century. In the 16th century, French Embassy moved to Beyoğlu. Due to the French Embassy located in the area and other embassies moved Beyoğlu too such as English, Holland, and the minority population in Beyoğlu has increased significantly in the 17th century. Beyoğlu was the center of the trade so its development accelerated in the 19th century, istiklal Avenue encircled by buildings mostly from late 19th and early 20th centuries that were designed with different architectural styles. The avenue begins with the Galata Tower, a medieval Genoese structure, and reach out to the Taksim Square. It retains its popularity and host crowds for years. During the Ottoman period, it was one of the most popular spot among Ottomans, Europeans and local Levantines. The cosmopolitan avenue is surrounded by significant buildings and spaces in terms of political, historical and social aspects such as Deveaux Apartments, Cercle d’Orient, Narmanh Han, Taksim Maksemi and Metro Han. Social structure and its changes have been influential in the production of cultural heritage. Between Galatasaray and Taksim has filled with entertainment places, casinos, hotels, theaters. Among these important structures there were also temporary spaces that produced for social functions such as entertainment. Entertainment areas were in the forefront of these temporary spaces with their miraculous objects and talented entertainers.This study seeks to explore the intangible dimensions of istiklal Avenue related to cultural memory/heritage and focus on underline them in terms of sustaining social identity. To examine this, study reveals personal and governmental archives, news from old newspapers and reminiscence of society. Also, it observes and analyses the current situation of the avenue and its future scenarios.
Keywords: Intangible Dimension; Heritage; Istiklal Avenue; Architectural Design; Cultural Memory